Cs1−xRbxSnI3 light harvesting semiconductors for perovskite photovoltaics. (13th June 2018) - Marshall, Kenneth P.; Tao, Shuxia; Walker, Marc; Cook, Daniel S.; Lloyd-Hughes, James; Varagnolo, Silvia; Wijesekara, Anjana; Walker, David; Walton, Richard I.; Hatton, Ross A.
Abstract : Partial substitution of Cs with Rb in CsSnI3 perovskite imparts useful increases in ionisation potential for photovoltaic applications. Abstract : We show that films of the 3-dimensional perovskite Cs1− x Rb x SnI3 can be prepared from room temperature N, N -dimethylformamide solutions of RbI, CsI and SnCl2 for x ≤ 0.5, and that for x ≤ 0.2 film stability is sufficient for utility as the light harvesting layer in inverted photovoltaic (PV) devices. Electronic absorption and photoluminescence spectroscopy measurements supported by computational simulation, show that increasing x increases the band gap, due to distortion of the lattice of SnI6 octahedra that occurs when Cs is substituted with Rb, although it also reduces the stability towards decomposition. When Cs0.8 Rb0.2 SnI3 perovskite is incorporated into the model inverted PV device structure; ITO|perovskite|C60 |bathocuproine|Al, an ∼120 mV increase in open-circuit is achieved which is shown to correlate with an increase in perovskite ionisation potential. However, for this low Rb loading the increase in band gap is very small (∼30 meV) and so a significant increase in open circuit-voltage is achieved without reducing the range of wavelengths over which the perovskite can harvest light. The experimental findings presented are shown to agree well with the predictions of density functional theory (DFT) simulations of the stability and electronic structure, also performed as part of this study.